EFFECT OF CLIMATE CHANGE ON CROP PRODUCTION IN INDIA (International Association of Biologicals and Computational Digest, 2022)
Agriculture and climate change are deeply intertwined. Crop production is highly sensitive to climate. It is affected by long-term trends in average rainfall and temperature, inter-annual climate variability, and extreme weather events. Climate change induced increases in temperatures, rainfall variation and the frequency and intensity of extreme weather events are adding to pressures on global agricultural and food systems. Climate change is expected to negatively affect both crop and livestock production systems in most regions, although some countries may actually benefit from the changing conditions. The changing climate is also adding to resource problems, such as water scarcity, pollution and soil degradation. Climate change is likely to contribute substantially to food insecurity in the future, by increasing food prices, and reducing food production. Climate change is already affecting agriculture, with effects unevenly distributed across the world. Future climate change will likely negatively affect crop production in low latitude countries, while effects in northern latitudes may be positive or negative. Climate change will probably increase the risk of food insecurity for some vulnerable groups, such as the poor. For example, South America may lose 1–21% of its arable land area, Africa 1–18%, Europe 11–17%, and India 20–40%. To manage the impact of climate change on agriculture, careful supervision of resources like soil, water and biodiversity is required.
Keywords: climate change, temperature increase, rainfall, extreme weather events, crop production, agriculture